Advancing Brain-Computer Interface Applications for Severely Disabled Children Through a Multidisciplinary National Network: Summary of the Inaugural Pediatric BCI Canada Meeting - Kinney-Lang, Eli; Kelly, Dion; Floreani, Erica D.; Jadavji, Zeanna; Rowley, Danette; Zewdie, Ephrem Takele; Anaraki, Javad R.; Bahari, Hosein; Beckers, Kim; Castelane, Karen; Crawford, Lindsey; House, Sarah; et al. (Frontiers in Human Neuroscience, 2020)
Thousands of youth suffering acquired brain injury or other early-life neurological disease live, mature and learn with only limited communication and interaction with their world. Such cognitively capable children are ideal candidates for brain-computer interfaces (BCI). While BCI systems are rapidly evolving, a fundamental gap exists between technological innovators and the patients and families who stand to benefit. Forays into translating BCI systems to children in recent years has revealed that kids can learn to operate simple BCI with proficiency akin to adults. BCI could bring significant boons to the lives of many children with severe physical impairment, supporting their complex physical and social needs. However, children have been neglected in BCI research and a collaborative BCI research community is required to unite and push pediatric BCI development forward. To this end, the pediatric BCI Canada collaborative network (BCI-CAN) was formed, under a unified goal to cooperatively drive forward pediatric BCI innovation and impact. This paper reflects on the topics and discussions raised in the foundational BCI-CAN meeting held in Toronto, Ontario in November 2019 and suggests the next steps required to see BCI impact the lives of children with severe neurological disease and their families.